Experimental study of stiffness fixation of a three-part fracture of the proximal humerus - Makarov, Vasyl; Lipovskiy, Volodymyr; Levadniy, Yevgen; Boyko, Igor; Lazarenko, Gleb (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The choice of the fixation method of proximal humerus fractures remains a controversial topic. Three- and four-part fractures are the most severe injuries in the spectrum of the proximal humerus fractures (types B and C for AO/OTA) are found in clinical practice in 20 % of patients, especially in patients over 60 years old with osteoporosis. Objective: a comparative study of stiffness fixation of three-part proximal humerus fractures on artificial osteoporotic models using various metal implants, including structural polylactic acid allograft. Methods: the biomechanical experimental study has been included 4 types of fragment fixation of artificial models. Type I — intramedullary blocked 7 mm titanium reconstructive cannulated nail, type II — four 5.0 mm cannulated screws with spongy thread; type ІІІ — PHILOS plate with reinforcement of the head fragment with 2 structural polylactic acid transplants (PLA); type IV — PHILOS plate without reinforcement allograft. Tests performed for three types of loading, depending on the angle of inclination of the bone in the frontal plane — 0°, 10°, and 20°. Results: The least load-bearing system «bone – implant» was found in type І, and the most — in type II, the difference between rigidity was 4 times. Structural rigidity in type IV was less than 2 times compared to type I and less by 10 % in comparison with type III. The value of the rigidity of the considered types of fixation with the increase of the angle of inclination of the axis of the bone in the frontal plane decreases. The highest carrying capacity, as well as the amount of deformation energy, was found for type III, and the smallest — for type I. Conclusions: according to biomechanical tudy the best method fixation of the three-part fracture of the proximal humerus is the type III — PHILOS plate with reinforcement with 2 structural polylactic acid grafts (PLA).